W/V Dual-Atom Doping MoS2-Mediated Phase Transition for Efficient Polysulfide Adsorption/Conversion Kinetics in Lithium–Sulfur Battery - Cui, Zhe; Feng, Ping; Zhong, Gang; Ou, Qingdong; Liu, Mingkai (Nano-Micro Letters, 2026)
The dissolvable polysulfides and sluggish Li2S conversion kinetics are acknowledged as two significant challenges in the application lithium–sulfur (Li–S) batteries. Herein, we introduce a dual-doping strategy to modulate the electronic structure of MoS2, thereby obtaining a multifunctional catalyst that serves as an efficient sulfur host. The W/V dual single-atom-doped MoS2 grown on carbon nanofibers (CMWVS) demonstrates a strong adsorption ability for lithium polysulfides, suppressing the shuttle effects. Additionally, the doping process also results in the phase transition from 2H-MoS2 to 1T-MoS2 and generates sufficient edge sulfur atoms, promoting the charge/electron transfer and enriching the reaction sites. All these merits contribute to the superior conversion reaction kinetics, leading to the outstanding Li–S battery performance. When fabricated as cathodes by compositing with sulfur, the CMWVS/S cathode delivers a high capacity of 1481.7 mAh g−1 at 0.1 C (1 C = 1672 mAh g−1) and maintains 816.3 mAh g−1 after 1000 cycles at 1.0 C, indicating outstanding cycling stability. Even under a high sulfur loading of 7.9 mg cm−2 and lean electrolyte conditions (E/S ratio of 9.0 μL mg−1), the cathode achieves a high areal capacity of 8.2 mAh cm−2, showing great promise for practical Li–S battery applications. This work broadens the scope of doping strategies in transition-metal dichalcogenides by tailoring their electronic structures, providing insightful direction for the rational development of high-efficiency electrocatalysts for advanced Li–S battery applications. Highlights: 1 W/V dual single-atom doping induces 2H−1T phase transition and boosts sulfur conversion kinetics. 2 Strong polysulfide adsorption effectively suppresses the shuttle effect. 3 CMWVS/S cathode delivers high specific discharge capacity (1481.7 mAh g−1 at 0.1 C) and excellent stability (816.3 mAh g−1 after 1000 cycles at 1.0 C), even under high sulfur loading.